EFFECTIVENESS OF COMPLEMENTARY FEEDING USING PUMPKIN AND BANANA-BASED SUPPLEMENTARY FOOD ON WEIGHT, MID UPPER ARM CIRCUMFERENCE (MUAC), AND ILLNESS FREQUENCY OF UNDERNOURISHED INFANTS AGED 6-12 MONTHS AT PAYUNG SEKAKI HEALTH CENTER IN 2023 - Vitriani, Okta; Alyensi, Fatiyani; Fadmiyanor, Isye (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2023)
Children under five years old (infants) are a vulnerable group prone to nutritional issues as their nutritional needs are crucial for supporting growth and development processes. Data from UNICEF and WHO in 2020 indicated that in 2020, 21.3% of infants worldwide experienced stunting, 6.9% suffered from wasting, and 13% had underweight issues. The Health Profile Data of Pekanbaru City in 2021 showed that the number of undernourished infants categorized as underweight amounted to 993, with the highest concentration within the jurisdiction of the Payung Sekaki Health Center, totaling 358 infants. Infant growth is influenced by various factors, one of which is nutrition, and for infants above 6 months, Complementary Feeding (CF) plays a significant role in boosting weight gain to support their growth and development. Bananas and pumpkins are local foods easily accessible and processed, both recommended as supplementary foods for infants. This research aims to identify the effectiveness of pumpkin and banana-based CF on weight gain, mid-upper arm circumference (MUAC), and illness frequency in undernourished infants aged 6-12 months. The study was conducted from February to September 2023 in the Payung Sekaki Health Center area in Pekanbaru City. The study design employed a Quasi-Experimental approach with a Two-Group Posttest design involving a sample of 30 infants. Based on the conducted research, it can be concluded that there is a significant difference in the average weight and MUAC before and after the intervention of pumpkin and banana-based CF. Additionally, pumpkin-based CF was more effective in increasing weight with a p-value (0.000) < α (0.05). Both pumpkin and banana-based CF contributed to weight gain, MUAC improvement, and reduced illness frequency among infants. This can be considered as a recommendation and health promotion strategy applicable to midwives, particularly for mothers with undernourished infants.